Improvement in electromagnetic interference shielding effectiveness of cement composites using carbonaceous nano/micro inerts. (15th June 2015) - Khushnood, Rao Arsalan; Ahmad, Sajjad; Savi, Patrizia; Tulliani, Jean-Marc; Giorcelli, Mauro; Ferro, Giuseppe Andrea
Highlights: Cost effective material to improve electromagnetic wave absorption was explored. Carbonaceous inerts were produced from hazelnut shell and peanut shell. Carbonized particles addition significantly enhanced EMI SE of cement composites. 0.5 wt% carbonized peanut shell addition showed the best results. Abstract: The current study is focused to explore a cost effective material for enhancing the electromagnetic interference shielding effectiveness of cement composites. Agricultural residue in the form of peanut and hazelnut shells having little or no economic value was investigated for the subject purpose. These wastes were pyrolyzed at 850 °C under inert atmosphere and ground to sub-micron-size before utilization with cement. Dispersion of sub-micron-carbonized shell was initially observed in water through visual inspection and later in cement matrix using FESEM micrographs of fractured composites. Results displayed that both carbonized peanut shell (CPS) and carbonized hazelnut shell (CHS) possess excellent ability to get easily dispersed in host medium. The complex permittivity of sub-micron-composites was measured in a wide frequency band (0.2–10 GHz) using a commercial dielectric probe (85070D) and network analyzer E8361A. Due to strong polarization resulting from well dispersed sub-micron carbonized shell inclusions, a significant increase in measured dielectric constant ( ε ′) and dielectric loss ( ε ″) of cement composites was observed with direct relation to the added content. Numerically evaluated values of electromagnetic interference shielding effectiveness showed remarkable improvement with the addition of sub-micron carbonized shells in cement composites. Maximum increase of 353%, 223%, 126% and 83% was observed in shielding effectiveness at 0.9 GHz, 1.56 GHz, 2.46 GHz and 10 GHz frequencies respectively, by adding only 0.5% CPS by weight of cement, in comparison to the pristine cement samples. Based on experimental results, it is concluded that the investigated material is highly cost effective (approx. 85% cost saving); very efficient in dispersion as compared to the carbon nanotubes (CNTs) or graphene and quite effective in enhancing the electromagnetic interference shielding properties of resultant cement composites.